KECERDASAN SPIRITUAL DALAM MAJELIS PESONA ILAHI PONOROGO - Iin Inayatussalamah (IAIN Ponorogo, 2015)
Abstract: Spiritual Knowledge is an essential part of the teachings atPesonaIlahi Assembly,Joresan-Mlarak, Ponorogo and this determines the assembly to receive tremendous public welcoming. What and how the spiritual knowledge is developed is very interesting to study. Through a qualitative approach, this study aimedat examining more deeply by employing in-depth interviews, observation, and documentation. In analyzing the data, interactive analysis was usedby adopting the concept of Miles and Hibermaninvolving three main stages: data reduction, data display, and conclusion. The results showed: 1). The emergence of the Assembly was determined by two factors: a) Murshid teachers,RomoKyaiLabibHudaf gained the trust fromRosulallah Saw to lead the people (Kholifahfilardi) and b) the emergence of spiritual aridity, growing akhlakulkarimah, making intelligent people spiritually. 2) there were four values of spiritual intelligence found: a) unifying motion and oral in the sense of wholeness, b) making a whole of senses in the natural subservience, and c) prioritizing the most important primary, and d) subjecting ideology in ideology. 3). The implementation of the congregation spiritual intelligence can be seen from: a) in a polite language and courteous behavior, b) khusnudzon and Qona’ah, c) subject to and obey the command of Murshid teacher, d) Tafakkur. 4) The contribution given was to foster the potential of spiritual intelligence that came from the human nature itself. ،وغورونوف كرلام ناسروج في “ يلهلإا بذلجا سلمج “ ميلعت نم مهم ءزج ةيونعلما ةيحورلا فراعلما نإ باّ ذج رمأ ميلاعتلا هذه ىَّ منٌ ت فيكو ميلاعتلا هذه يه ام .سللمجا اذه دوجو عمتلمجا نم يرثك باجتسا اذهبف ،ةقيمعلا ةلباقلما : بيلاسأب اهيف ةقيمعلا ةساردلا – يفيكلا لخدلماب – ثحبلا اذه لواح .هيف ثحبلل نامبرهو سليم همّ دق يذلا بولسلأا – تانايبلا ليلتح في – ثحابلا مدختسا .ةبوتكلما قئاثولاو ،ةظحلالماو .ثحبلا جئاتن جاتنتسا مث ،تانايبلا ضرعو ،تانايبلا ضيفتخ :تاوطلخاب ىلع دشرلما خيشلا لوصح : لولأا ،نلاماع سللمجا اذه روهظ ةيفلخ نإ )1 : يلاتلاك ثحبلا جئاتنو يحورلا فافلجا ةرهاظ ءوشن : يناثلاو ،)ضرلأا في ةفيلخ( ةملأا سيئر نوكيل )م -ص( لوسرلا نم ةناملأا : يحورلا ءاكذلل ميق عبرأ ةثمو )2 .اّ يحور ّ يكذلا ناسنلإا نيوكتو ،قلاخلأا مراكم ةيمنتو ،عمتلمجا في ليضفت ،ثلاثلا ،لماعلا عوضخ في روعشلا ديحوت ،يناثلاو ،روعشلا ةدحو في قطنلاو ةكرلحا ديحوت ،لولأا ىدل ّ يحورلا ءاكذلاو ميقلا هذه قيبطت امأ )3 .مهفلا في مهفلا عيضتخ ،عبارلا ،ةلضافلا ءايشلأا نم لضفلأا قلاخأب ينقلختمو ابدأتم انّ يل انسح املاك مهملاك ،لولأا : في ةرهاظف سللمجا اذه لىإ ةبستنلما ةعاملجا نييدلا مهسلا امأ )4 .رّ كفتلا ،عبارلاو ،دشرلما خيشلا ةعاط ،ثلاثلاو .ةعانقلاو ّ نظلا نسح ،يناثلاو .ةيمرك.هسفن ناسنلإا ةرطف نم ةتجانلا يحورلا ءاكذلا ةقاط ةيمنت وه سللمجا اذه نم